Botani, Manfaat, dan Bioaktivitas Nilam Pogostemon cablin - Marina Silalahi (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kristen Indonesia, 2019)
Pogostemon cablin (PC) is a belonging of Lamiaceae which produces a distinctive aroma known as patchouli oil which is used in the production of perfumes and as aroma therapy. The aroma produced by plants is related to the content of volatile secondary metabolites. The writing of this article is based on literature studies in the form of books, journals and other research results and then synthesized to obtain comprehensive information about botany and the use of PCs. In Indonesia, there are three types of Pogostemon, namely PC (Aceh patchouli), P. heyneatus (Javanese patchouli) and P. hortensis (patchouli soap), but what produces more patchouli oil is a PC. Patchouli oil is a essential oil from PC leaves which is used in the pharmaceutical industry and has a very high economic value. In traditional medicine PC used to cure fever, nausea, colds, headaches, fever, nausea, vomiting, diarrhea, stomach ache, insect bites and snakes. The alcohol patchouli, Î±-patchoulene, Î²-patchoulene, Î±-bulnesene, seychellene, norpatchoulenol, pogostone, eugenol and pogostol are the main essential oils of PCs. Bioactivity of the PC is anti-stress, anti-influenza, aroma therapy, antioxidant and anti-microbial. The use of PC as aroma therapy needs to be studied further so that it can be developed in commercial scale to sauna. Keywords: Pogostemon cablin, patchuoli oil, aroma therapy